2000
DOI: 10.1152/ajplung.2000.279.6.l1091
|View full text |Cite
|
Sign up to set email alerts
|

Lung function, permeability, and surfactant composition in oleic acid-induced acute lung injury in rats

Abstract: Although acute lung injury (ALI) is associated with inflammation and surfactant dysfunction, the precise sequence of these changes remains poorly described. We used oleic acid to study the pathogenesis of ALI in spontaneously breathing anesthetized rats. We found that lung pathology can occur far more rapidly than previously appreciated. Lung neutrophils were increased approximately threefold within 5 min, and surfactant composition was dramatically altered within 15 min. Alveolar cholesterol increased by appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 50 publications
7
40
0
Order By: Relevance
“…Schmidt et al pointed out changes in the ratio of saturated fatty acid and unsaturated fatty acid in the BALF of 39 patients with acute respiratory distress syndrome (ARDS) and reported a decrease in the patients' lung surface tension with administration of phosphatidylcholine, the main component of saturated fatty acid 22) . In addition, Davidson et al pointed out reduced lung compliance in rats with acute lung obstructions and reported a difference in unsaturated fatty acid concentration 23) . We could not find any experiments like ours that assessed surfactant function by BALF surface tension.…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt et al pointed out changes in the ratio of saturated fatty acid and unsaturated fatty acid in the BALF of 39 patients with acute respiratory distress syndrome (ARDS) and reported a decrease in the patients' lung surface tension with administration of phosphatidylcholine, the main component of saturated fatty acid 22) . In addition, Davidson et al pointed out reduced lung compliance in rats with acute lung obstructions and reported a difference in unsaturated fatty acid concentration 23) . We could not find any experiments like ours that assessed surfactant function by BALF surface tension.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to note that more recent evidence suggests that plasma proteins may have less effect on the surface tension lowering capacity of surfactant (35,41) than originally believed. In fact cholesterols, elevated to the levels measured in the airways of subjects with ALI (14,44), more prominently inhibit the surface tension lowering effects of surfactant in vitro than do serum proteins (21), a disparity that could also apply in vivo. With this in mind, it is curious to note that most studies reporting improved lung function with the use of fibrinolytic agents in ALI have focused predominantly on ventilationperfusion matching and oxygenation (2,16,50,57), with limited reporting on changes in lung mechanical function.…”
Section: Discussionmentioning
confidence: 99%
“…At the termination of the experiment, rats were anesthetized by intraperitoneal injection with 0.25% pentobarbital sodium at 40 mg/kg at each time point. [18] …”
Section: Preparation Of the Animal Modelmentioning
confidence: 99%